2016
DOI: 10.18203/2320-6012.ijrms20160527
|View full text |Cite
|
Sign up to set email alerts
|

Role of multidetector computed tomography in evaluation of suspected bronchogenic carcinoma

Abstract: INTRODUCTIONBronchogenic carcinoma was considered to be rare in the beginning of the century but has now reached epidemic proportions. This dramatic increase correlates with the widespread prevalence of cigarette smoking.1 Lung cancer is the leading cause of cancer mortality for both men and women, responsible for more deaths than prostate, breast, and colorectal cancers combined.2 Physical symptoms such as fever, cough, expectoration, haemoptysis, weight loss and anorexia are common to lung cancer. However, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
2
4
1
Order By: Relevance
“…This is in concordance with the study by Malik PS et al 6 (2013), Krishnamurthy A et al 12 (2012), Shad D et al 7 (2017), Dr. Modi M et al 19 (2016) and Dr. Babu S et al 5 (2016) which showed an increasing trend in the incidence of adenocarcinoma. However, our findings are contrary to the studies done by Dr. Adaikkalavan et al 18 (2017), Rawat J et al 10 (2009), Saket RK et al 1 (2016) and Yadav D et al 4 (2016) which revealed that squamous cell carcinoma was the most common histological subtype followed by adenocarcinoma.…”
Section: Histopathologycontrasting
confidence: 99%
“…This is in concordance with the study by Malik PS et al 6 (2013), Krishnamurthy A et al 12 (2012), Shad D et al 7 (2017), Dr. Modi M et al 19 (2016) and Dr. Babu S et al 5 (2016) which showed an increasing trend in the incidence of adenocarcinoma. However, our findings are contrary to the studies done by Dr. Adaikkalavan et al 18 (2017), Rawat J et al 10 (2009), Saket RK et al 1 (2016) and Yadav D et al 4 (2016) which revealed that squamous cell carcinoma was the most common histological subtype followed by adenocarcinoma.…”
Section: Histopathologycontrasting
confidence: 99%
“…The average age of our patients was 63 years, with male predominance, which is similar to that reported in other Indian studies conducted by Prasad et al 8 (57 years), Dey et al 9 (60.37 years), and Kaur et al 10 (58.6 years). The male to female ratio was 6.1:1, which is similar to that found in other studies conducted in India by Viswanathan et al 11 (ratio: 6.9:1) and Yadav et al 12 (ratio: 6:1).…”
Section: Discussionsupporting
confidence: 90%
“…Out of all patients 73 % patient had enlarged mediastinal lymph nodes, 51 % had subcarinal and 44 % had hilar lymph node involvement. There were similar findings seen in study done by Yadav et al 18 The amount of enhancement of 100 lung nodules were studied by measuring the CT numbers of both benign and malignant nodules on both pre contrast scan and post contrast scan showing maximum enhancement. There was no statistically significant difference between heterogeneity of contrast enhancement.…”
Section: Discussionsupporting
confidence: 74%